Calmodulin binds to the N-terminal domain of the cardiac sodium channel Nav1.5. Issue 1 (1st January 2020) - Wang, Zizun; Vermij, Sarah H.; Sottas, Valentin; Shestak, Anna; Ross-Kaschitza, Daniela; Zaklyazminskaya, Elena V.; Hudmon, Andy; Pitt, Geoffrey S.; Rougier, Jean-Sébastien; Abriel, Hugues
ABSTRACT: The cardiac voltage-gated sodium channel Nav 1.5 conducts the rapid inward sodium current crucial for cardiomyocyte excitability. Loss-of-function mutations in its gene SCN5A are linked to cardiac arrhythmias such as Brugada Syndrome (BrS). Several BrS-associated mutations in the Nav 1.5 N-terminal domain (NTD) exert a dominant-negative effect (DNE) on wild-type channel function, for which mechanisms remain poorly understood. We aim to contribute to the understanding of BrS pathophysiology by characterizing three mutations in the Nav 1.5 NTD: Y87C–here newly identified–, R104W, and R121W. In addition, we hypothesize that the calcium sensor protein calmodulin is a new NTD binding partner. Recordings of whole-cell sodium currents in TsA-201 cells expressing WT and variant Nav 1.5 showed that Y87C and R104W but not R121W exert a DNE on WT channels. Biotinylation assays revealed reduction in fully glycosylated Nav 1.5 at the cell surface and in whole-cell lysates. Localization of Nav 1.5 WT channel with the ER did not change in the presence of variants, as shown by transfected and stained rat neonatal cardiomyocytes. We demonstrated that calmodulin binds the Nav 1.5 NTD using in silico modeling, SPOTS, pull-down, and proximity ligation assays. Calmodulin binding to the R121W variant and to a Nav 1.5 construct missing residues 80–105, a predicted calmodulin-binding site, is impaired. In conclusion, we describe the new natural BrS Nav 1.5 variant Y87C and present first evidence that calmodulin binds to the Nav 1.5 NTD, which seems to be a determinant for the DNE.